ANALISIS PERENCANAAN PENGEMBANGAN EKONOMI KREATIF DI DINAS PARIWISATA, KEBUDAYAAN, KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Dhesti Widya Nurhasanah Ningrum; Delia Khoerunisa; Fitriyani; Karlina Ratnadewi; Usep Hidayat (JRPA - Journal of Regional Public Administration, 2021)
Creative economy is an economic concept in the new economic era that intensifies information and creativity, by prioritizing ideas and knowledge from human resources, as the main production factor. The purpose of this research is to see what factors and efforts are made in overcoming the obstacles to planning the development of the creative economy in the tourism and sports office of Sumedang Regency. This study took 5 (five) respondents. Data collection methods used interview and observation techniques. The interview technique was conducted in an unstructured manner using interview guidelines. The observation technique was carried out by two observers. The research data analysis is descriptive. The implementation of activities and the preparation of creative economy development planning in the youth tourism and sports office of Sumedang Regency is still weak, this picture can be seen from how public knowledge related to the creative economy and the implementation of activities where the information provided is not comprehensive and the planning method is still less directional. Efforts are made in Administrative Difficulties by maximizing good administration and in accordance with existing rules and needs.